Strategies for prevention of lower limb post-amputation pain: A clinical narrative review - Vanita Ahuja; Deepak Thapa; Babita Ghai (Wolters Kluwer Medknow Publications, 2018)
Postamputation limb pain or phantom limb pain (PLP) develops due to the complex interplay of peripheral and central sensitization. The pain mechanisms are different during the initial phase following amputation as compared with the chronic PLP. The literature describes extensively about the management of established PLP, which may not be applicable as a preventive strategy for PLP. The novelty of the current narrative review is that it focuses on the preventive strategies of PLP. The institution of preoperative epidural catheter prior to amputation and its continuation in the immediate postoperative period reduced perioperative opioid consumption (Level II). Optimized preoperative epidural or intravenous patient-controlled analgesia starting 48 hours and continuing for 48 hours postoperatively decreased PLP at 6 months (Level II). Preventive role of epidural LA with ketamine (Level II) reduced persistent pain at 1 year and LA with calcitonin decreased PLP at 12 months (Level II). Peripheral nerve catheters have opioid sparing effect in the immediate postoperative period in postamputation patients (Level I), but evidence is low for the prevention of PLP (Level III). Gabapentin did not reduce the incidence or intensity of postamputation pain (Level II). The review in related context mentions evidence regarding therapeutic role of gabapentanoids, peripheral nerve catheters, and psychological therapy in established PLP. In future, randomized controlled trials with long-term follow-up of patients receiving epidural analgesia, perioperative peripheral nerve catheters, oral gabapentanoids, IV ketamine, or mechanism-based modality for prevention of PLP as primary outcome are required.